Safe prescription of systemic antineoplastic treatment in oncology: integrative literature review - Fabiola Vasconcelos Alves; Renata Cristina de Campos Pereira Silveira; Flavia Oliveira de Almeida Marques da Cruz; Elaine Barros Ferreira; Paula Elaine Diniz dos Reis (Brazilian Journal of Oncology)
The objective of this study was to identify the available evidence on the parameters that should be considered to improve the quality and safety of the prescription of systemic antineoplastic treatment. This is an integrative review carried out in the EMBASE, LILACS, and PubMed databases, from 2015 to 2019. The methodological quality of the included studies was assessed by the tools of the Joanna Briggs Institute. Eight studies were included, of which 5 addressed adverse events related to systemic antineoplastic treatment, including 4,970 patients treated with immunotherapy, target therapy, and chemotherapy. One study assessed the safety of prescribing antineoplastic agents and 2 studies addressed pharmacovigilance and risk management by assessing treatment- related adverse effects. Chemotherapy, target therapy, and immunotherapy have different toxicity profiles. The evidence suggests that assessment of treatment toxicity as well as risk management should be considered to improve the quality and safety of prescribing systemic antineoplastic treatment.